Anatomy and classification of the posterior tibial fragment in ankle fractures - Bartoníček, Jan; Rammelt, Stefan; Kostlivý, Karel; Vaněček, Václav; Klika, Daniel; Trešl, Ivo (Archives of orthopaedic and trauma surgery, 2015)
INTRODUCTION: The aim of this study was to analyze the pathoanatomy of the posterior fragment on the basis of a comprehensive CT examination, including 3D reconstructions, in a large patient cohort. MATERIALS AND METHODS: One hundred and forty one consecutive individuals with an ankle fracture or fracture-dislocation of types Weber B or Weber C and evidence of a posterior tibial fragment in standard radiographs were included in the study. The mean patient age was 49 years (range 19-83 years). The exclusion criteria were patients below 18 years of age, inability to provide written consent, fractures of the tibial pilon, posttraumatic arthritis and pre-existing deformities. In all patients, post-injury radiographs were obtained in anteroposterior, mortise and lateral views. All patients underwent CT scanning in transverse, sagittal and frontal planes. 3D CT reconstruction was performed in 91 patients. RESULTS: We were able to classify 137 cases into one of the following four types with constant pathoanatomic features: type 1: extraincisural fragment with an intact fibular notch, type 2: posterolateral fragment extending into the fibular notch, type 3: posteromedial two-part fragment involving the medial malleolus, type 4: large posterolateral triangular fragment. In the 4 cases it was not possible to classify the type of the posterior tibial fragment. These were collectively termed type 5 (irregular, osteoporotic fragments). CONCLUSION: It is impossible to assess the shape and size of the posterior malleolar fragment, involvement of the fibular notch, or the medial malleolus, on the basis of plain radiographs. The system that we propose for classification of fractures of the posterior malleolus is based on CT examination and takes into account the size, shape and location of the fragment, stability of the tibio-talar joint and the integrity of the fibular notch. It may be a useful indication for surgery and defining the most useful approach to these injuries.
Keywords: Young Adult; zobrazování trojrozměrné; Male; počítačová rentgenová tomografie; mladý dospělý; fraktury kotníku; Adult; Aged; dospělí; fraktury tibie; mužské pohlaví; senioři; Tarsal Bones; Imaging, Three-Dimensional; Tibia; tarzální kosti; Tomography, X-Ray Computed; senioři nad 80 let; lidé; ženské pohlaví; Humans; Tibial Fractures; Ankle Fractures; Aged, 80 and over; Female; lidé středního věku; tibie; Middle Aged